Protection of boron nitride nanosheets by atomic layer deposition toward thermal energy management applications. (October 2017) - Luo, Wei; Zhou, Lihui; Yang, Zhi; Dai, Jiaqi; Hitz, Emily; Kuang, Yudi; Han, Xiaogang; Yang, Bao; Hu, Liangbing
Abstract: Hexagonal boron nitride ( h -BN), a material with long-known excellent thermal and chemical stability, has emerged as one of the most attractive two-dimensional materials for thermal energy management applications. However, recent discoveries revealed that oxidation of h -BN occurs at relatively low temperature due to the existence of defects on h -BN flakes. Herein, we propose a route to protect h -BN from oxidation at temperatures up to 1000 °C by a thin layer of Al2 O3 via atomic layer deposition (ALD). The ALD-Al2 O3 layer terminates the defects of BN and maintains BN intact at 1000 °C under ambient atmosphere. In addition, a thermally conductive and electrically insulating glass has been demonstrated through a facile solution-processed BN nanosheets spray coating and subsequent Al2 O3 deposition by ALD. The ALD-Al2 O3 layer effectively glued the BN nanosheets and increased the adhesion between BN layer and glass, which enabled a high thermal conductivity of 4.55 W/m K while the bare glass shows a low thermal conductivity of 0.94 W/m K. Furthermore, with the BN and ALD-Al2 O3 coating, more uniform temperature distribution was obtained on the glass. We believe the coating approach by using BN and ALD technology is potentially competitive for scaling up in thermal energy management or high temperature applications. Graphical abstract: Highlights: Pits and holes appear on pristine BN flakes at high temperature. Well-defined, monodispersed holes can be obtained on BN. A thin Al2 O3 layer by ALD plays a protective role for improving the thermal stability of BN flakes. A thermally conductive, electrically insulating glass can be achieved based on BN and ALD.